Strategi Mengurangi Rasa Bosan Anak Selama SFH (School From Home) Melalui Kegiatan Berkebun dengan Sistem Vertikultur di Dusun IV Desa Manik Maraja Kecamatan Sidamanik Kabupaten Simalungun - Mavianti, Mavianti; Dwi Ananda, Rizky (Maslahah: Jurnal Pengabdian Masyarakat, 2020)
Since the implementation of school from home or learning from home for every level of education, and PAUD children are no exception, it often causes boredom. Boredom that appears should not be allowed and must be overcome immediately. The purpose of this service is to reduce the boredom that arises in children with gardening activities through the verticultural system. The method used is through 3 (three) stages, namely the preparation stage, the implementation stage and the evaluation stage. The result of this activity was that the participants, consisting of PAUD and elementary school children in grades 1 and 2, were very enthusiastic about participating in this activity. This can be seen by the children being very enthusiastic and serious about listening to and paying attention to the exposure of the speakers. Moreover, related to gardening with a verticulture system using paralon pipes, this was the first time they knew about it